2017
DOI: 10.3389/fphar.2017.00036
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Late Na and Ca Currents as Effective Antiarrhythmic Drug Targets

Abstract: While recent advances clarified the molecular and cellular modes of action of antiarrhythmic drugs (AADs), their link to suppression of dynamical arrhythmia mechanisms remains only partially understood. The current classifications of AADs (Classes I, III, and IV) rely on blocking peak Na, K and L-type calcium currents (ICa,L), with Class II with dominant beta receptor blocking activity and Class V including drugs with diverse classes of actions. The discovery that the calcium and redox sensor, cardiac Ca/calmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 112 publications
(188 reference statements)
2
53
0
Order By: Relevance
“…The potent suppressive effect of GS-967 against oxidative AF provides a novel class of antiarrhythmic drug action not considered in previous drug action classification [11]. Interestingly, recent studies demonstrated, consistent with the results of the present study, that increased I Na-L plays a key role in the induction of rapid pacing-induced AF in mice and its suppression by GS-967 [31].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The potent suppressive effect of GS-967 against oxidative AF provides a novel class of antiarrhythmic drug action not considered in previous drug action classification [11]. Interestingly, recent studies demonstrated, consistent with the results of the present study, that increased I Na-L plays a key role in the induction of rapid pacing-induced AF in mice and its suppression by GS-967 [31].…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, recent studies demonstrated, consistent with the results of the present study, that increased I Na-L plays a key role in the induction of rapid pacing-induced AF in mice and its suppression by GS-967 [31]. The importance of I Na-L blockade in the suppression of AF with the novel specific I Na-L blocker, eleclazine was also demonstrated in larger animals (pigs) [32] indicating the potential antiarrhythmic efficacy of this new class of drug action in humans [11]. …”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…EADs are usually, but not exclusively, associated with excessive AP prolongation (e.g. by increased inward I Ca,L 37 and late Na + -current I Na,L or I NCX , 38, 39 or by reduced K + -currents (I K ), allowing I Ca,L to recover from inactivation and depolarize the cardiomyocyte by allowing Ca 2+ to enter. 40 CaMKII-dependent I Ca,L phosphorylation slows inactivation and accelerates recovery from inactivation, further enhancing the likelihood of EADs.…”
Section: Fundamental Arrhythmia Mechanismsmentioning
confidence: 99%
“…Drugs that act on voltage-gated ion channels have for long been used as a treatment for many diseases, even before we knew such channels existed, in particular to control diseases of excitability (Brodie, 2010;Karagueuzian et al, 2017). Historically, natural compounds found in plants and toxins from animals have also been used to gain a better understanding of the structure and function of voltage-gated ion channels (Agnew et al, 1978;Cestèle and Catterall, 2000;MacKinnon, 1991;Stevens et al, 2011).…”
Section: Voltage-gated Ion Channels As Pharmacological Targetsmentioning
confidence: 99%